Deep neuromuscular blockade during radiofrequency catheter ablation under general anesthesia reduces the prevalence of atrial fibrillation recurrence when compared to moderate neuromuscular blockade: A randomized controlled trial - Eun Jung Oh; Jae-Geum Shim; Suyong Jeon; Eun Ah Cho; Sung Hyun Lee; Taeho Jeong; Jin Hee Ahn (PLoS ONE, 2025)
Background Proper anesthesia management is required to maintain immobilization and stable breathing of the patient to improve catheter contact and stability during catheter ablation for PVI. However, it remains unclear whether the depth of neuromuscular blockade affects the results of RFCA under general anesthesia. Methods The patients were randomly assigned to either the moderate neuromuscular blockade group (Group M, train-of-four 1 to 2) or the deep neuromuscular blockade group (Group D, posttetanic count 1–2). The primary outcome was the 12-month AF recurrence rate using confirmed electrocardiographic diagnosis after the ablation procedure at two different neuromuscular blockade depths. Results Total 94 patients (47 in each group) were included in the analysis. Recurrence of AF during the A 12-month follow-up was 12 (25%) in group D and 22 (46%) in group M. The AF recurrence rate was significantly higher in group M (p =  0.03). The relative risk (RR) for the risk of 12-month AF recurrence was 0.545 in group D. AF symptom recurrence was observed during the A 12-month follow-up in 12 (25%) and 26 (54%) patients in groups D and M, respectively. Conclusions Compared to moderate neuromuscular blockade, deep neuromuscular blockade while performing RFCA under general anesthesia reduced 12-month AF recurrence rate. Deep neuromuscular blockade under general anesthesia is thought to increase the success rate by providing a stable surgical environment during the RFCA procedure. Trial registration Clinical trials of Korea KCT 0003371